2012
DOI: 10.1167/iovs.12-8303
|View full text |Cite
|
Sign up to set email alerts
|

Development of Retinal Pigment Epithelium from Human Parthenogenetic Embryonic Stem Cells and MicroRNA Signature

Abstract: hPESCs can develop into RPE-like cells and, thus, can be additional promising sources of RPE cells in cell therapy. The miR-204, miR-302s, and their targets are involved in regulating directed differentiation during the full course, thereby contributing to the search for a new method of improving differentiation efficiency using miRNAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…A large body of evidence indicates that miR-204 plays a crucial role in the differentiation and function of all of the ocular structures in which it is expressed. In vitro assays have shown that miR-204 may be involved in the correct differentiation and function of RPE cells (27,29,30). MiR-204 is also required for proper lens development (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…A large body of evidence indicates that miR-204 plays a crucial role in the differentiation and function of all of the ocular structures in which it is expressed. In vitro assays have shown that miR-204 may be involved in the correct differentiation and function of RPE cells (27,29,30). MiR-204 is also required for proper lens development (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…Mitf also transactivates expression of miRNAs, and the dynamic regulation of miRNA expression is strongly associated with RPE differentiation; e.g. miR-204 and miR-211 (Adijanto et al, 2012; Hu et al, 2012; Li et al, 2012; Wang et al, 2010a). …”
Section: Overview Of Early Eye Development and Rpe Specificationmentioning
confidence: 99%
“…Complexity in the regulatory network between miRNAs and their processing factors has, to certain extents, limits comprehensive and thorough investigations. MiRNAs’ roles in the survival and function of RPE cells have been previously annotated, while their roles in RPE differentiation are still unclear [15, 16]. MiR-184 , located on 15q25.1, is an evolutionarily conserved non-coding RNA oligo.…”
Section: Introductionmentioning
confidence: 99%